Koenigsberger H. G., Estates and Revolutions. Essays in Early Modern European History - Górski, Karol (Czasopismo Prawno-Historyczne, 1972)
Recenzja: H. G. Koenigsberger, Estates and Revolutions. Essays in Early Modern European History. Cornell Univ. Press, Ithaca and London 1971.